Self-efficacy, alertness and work-family conflict toward women entrepreneurial success - Maliani, Mohamad; Rusnifaezah, Musa; Azizi, Abu Bakar; Siti Nur Zahirah, Omar; Razli, Ramli; Che Mohd Syaharuddin, Che Cob (World Scientific and Engineering Academy and Society, 2024)
Over the last few decades, the rise in women's entrepreneurship has been influenced by greater access to education, changing societal attitudes, advancements in technology, and initiatives aimed at empowering women in the business world. The increasing number of women entrepreneurs worldwide, is attributed to technological advancements and a decrease in job opportunities in both government and private sector. As a developing country, Malaysia also has a considerable number of women entrepreneurs taking advantage of entrepreneurial opportunities due to limited prospects and desire to have more quality time with their families. This research delves into the correlation between self-efficacy, alertness, and work-family conflict toward the success of women entrepreneurs. Recognizing that women play a crucial role in family management and business, this study investigates the moderating effect of work-family conflict on the relationship between self-efficacy, alertness, and the success of 300 women entrepreneurs in Malaysia. 300 successful women entrepreneurs participated through an online survey method and the data gathered were analyzed through the Statistical Package of Social Science (SPSS) version 22 and SmartPLS 3.0.